Changes in cardiovascular health and physical fitness in ethnic youth with intellectual disabilities participating in a park‐based afterschool programme for two years. Issue 6 (20th June 2019) - Messiah, Sarah E.; D'Agostino, Emily M.; Patel, Hersila H.; Hansen, Eric; Mathew, Matthew Sunil; Arheart, Kristopher L.
Abstract: Background: Youth with intellectual disabilities are more likely to be an unhealthy weight and less physically active than youth without intellectual disability. Objective: The effects of Fit2Play, a park‐based afterschool programme on cardiovascular/fitness health outcomes among youth with intellectual disability, were prospectively assessed. Methods: Youth ages 6 to 22 with intellectual disability who participated in Fit2Play for either one or two school years between 2010 and 2016 ( N  = 297, mean age 14.1 years, 70% Hispanic, 20% non‐Hispanic black, 72% male) were examined via a fitness battery at the beginning/end of the school year(s). Effects of length of Fit2Play participation on body mass index (BMI) %ile, skinfold thicknesses, systolic/diastolic blood pressure (SBP/DBP) %iles, fitness tests, and health and wellness knowledge) were evaluated via two‐level repeated measures analysis adjusted for child gender, age, ethnicity and area‐level poverty. Results: Adjusted models showed that up to two years of Fit2Play participation was significantly associated with improved BMI %ile, skinfold thicknesses, SPB/DBP %iles and PACER scores ( p  < 0.05 for all). One and two years of programme participation was associated with a 6% [95% CI: 0.92, 0.96] and 10% [95% CI: 0.87, 0.93] reduction in SBP%ile, respectively ( p  < 0.001), and a 36% [95% CI: 1.28, 1.45] and 57% [95% CI: 1.44, 1.70] increase in PACER score laps, respectively, compared to baseline. Conclusions: Results here suggest that park‐based, structured afterschool programmes with a focus on health and wellness can be a rich resource for this nation by offering both exclusive and immersion programmes for children with intellectual disability to foster cardiovascular health in all youth.